Menanamkan Nilai-Nilai Tasamuh untuk Menangkal Paham Radikalisme di Taman Pendidikan Al-Qur'an (TPQ) Perspektif Psikologi Pendidikan Islam - saliyo, saliyo (THUFULA, 2020)
Abstract : INSTILLING THE VALUES OF TASAMUH (TOLERANCE) TO DENY THE UNDERSTANDING OF RADICALISM IN THE AL-QUR’AN EDUCATION PARK (TPQ) PSYCHOLOGICAL PERSPECTIF OF ISLAMIC EDUCATION. This empowerment and dedication research aims to find out the education of tasamuh (tolerance) in the Al-Qur'an Education Park (TPQ). The research method uses the Participatory Action Research (PAR) method. Researchers directly involved in research objects involved in learning activities. Researchers interact directly with the board of asatidz and students in the TPQ. Retrieval of research data using interviews, observation, and document data. The informant taking strategy uses non probability sampling. The collection technique uses purposive sampling. The results showed that the education of the Al-Qur'an Al Itqan Ngembalkulon Kudus showed that education concentrated on cognitive and emotive. Cognitive education contains material related to the science of reading the Qur'an and the procedures for prayer and prayer in daily activities. Educational material and emotive practices in daily life related to science and moral practices. Education is in the frame of behavior modification (behavior modification) and cognitive behavior (cognitive behavior).